Behavior of morbidity and mortality due to human immunodeficiency virus/AIDS in Nuevitas, Camagüey, 1993-2021 - Yoan Miguel Aguilar Duret; Leida Nilda Sifontes Viñas; María Esther Del Toro Rodríguez; Adonis Cintras Dones; Yenlys Laucraf Primelles (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation:  infection by human immunodeficiency virus/AIDS is considered the most fearsome of sexually transmitted infections. The studies related to the subject allow the approach to the different contexts and populations affected by this disease. Objective: to determine the behavior of morbidity and mortality related to the human immunodeficiency virus/AIDS. Methods: a retrospective descriptive study was carried out in the Nuevitas municipality,  from 1993 to 2021, which included 92 patients diagnosed with the human immunodeficiency virus/AIDS. The data were taken from the case registry of the Municipal Hygiene and Epidemiology Unit, and from individual epidemiological histories. The analyzed variables: year of diagnosis, age groups, sex, marital status, sexual orientation, way of detecting the disease and evolution. Results: an upward trend of cases was observed until December 2021. The most numerous age group was 20-24 years old, and the male sex predominated. At the disease time of diagnosis, the marital status of single prevailed, as well as the homosexual sexual orientation. Conclusions: in general, there was a tendency to increase the number of infected patients, mainly young single men, homosexuals; in addition, seropositives prevailed.